THE RISK MANAGEMENT APPROACH AS A MECHANISM TO REDUCE THE FINANCIAL RISKS FACING FINANCIAL INSTITUTIONS - ‬‏Asad Asad, Dr.Zeinab; Elsayed yaaqob, Dr.Omar (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2022)
This research mainly aims to submit a proposed form to use the risk management approach in the face of financial risks. To achieve the goal of the research, previous studies were analyzed in the field of research to find out what accounting literature has reached in this field and use it in create the proposed research model. The study reached a set of results, one of the importants of it is creating a proposed model for financial risk management It helps the financial management to improve its performance in identifying, analyzing and evaluating those risks and taking the necessary actions to remedy them.